THE GROWTH PERFORMANCE OF JUVENILE YELLOW FIN SEABREAM (A CANTHOPAGRUS ARABICUS) FED AT DIFFERENT FEEDING RATES WHILE REARED IN FLOATING NET CAGES - N. Ahmad; P. J. A. Siddiqui; K. M. Khan; N. U. Akbar; M. Rashid; R. Masroor (Journal of Animal and Plant Sciences, 2018)
This study investigated feeding management of yellowfin seabream, Acanthopagrus arabicus, juveniles under different feeding rates and its relationship to growth performance, survival, cannibalism and body composition. Thirty healthy fish 3 (21.87±0.22g initial weight) were stocked in 12 separate net cages 3.4m assigned to four groups: F1, F2, F3, and F4 to receive feed at 3%, 5%, 7% and 9% body weight per day (bw/d). The juveniles were fed twice daily with a diet containing 42% protein for seven weeks. At the end of the feeding trial, group F3, fed at 7% bw/d, had significantly (P< 0.05) higher percent weight gain, average daily weight gain and specific growth rate, followed by groups F2 (5% bw/d) and F4 ( 9% bw/d). The poorest growth performance was recorded in F1 ( 3% bw/d) . Cannibalism was not seen in any treatment group, and survival was recorded 100%. In the whole fish body proximate composition, protein, ash and moisture showed no change while lipid levels in the fish bodies increased with increasing feeding ratio. Based on the results, 7% bw/d was the optimum feeding rate for A. arabicus under given experimental conditions.
Keywords: Yellowfin seabream; growth performance; feeding rates; body composition; floating net cages.